IMPACT OF PHOTOPERIOD ON CIRCADIAN CARBOHYDRATE AND AMYLASE RHYTHMS IN THE DIGESTIVE SYSTEM OF SILKWORM, BOMBYX MORI - E. BHUVANESWARI,; S. SIVAPRASAD, (The Bioscan, 2012)
The impact of photoperiod on circadian carbohydrate and amylase rhythms was studied in the digestive system of Bombyx mori under 12h light -dark cycle (LD), continuous light (LL) and continuous dark (DD) conditions. The peaks in phase response curves were interpreted as carbohydrate (CS) and amylase synthetic (AS) cycles in gut wall and carbohydrate uptake (CU) and amylase release (AR) cycles in gut content while the interval between peaks and troughs as duration of such cycles. The carbohydrate rhythm included 6 CS cycles of 4h duration each under LD, 8 cycles of 3h duration each under LL and 7 cycles of 3.4h duration each under DD in gut wall and 8 CU cycles of 3h duration each under LD and DD and 6 cycles of 4h duration each under LL in gut content. The amylase rhythm maintained 7 AS cycles of 3.4h duration each under LD and DD and 9 cycles of 2.6h each under LL in gut wall and 8 AR cycles of 3h duration each under LD and LL and 6 cycles of 4.0h duration each under DD in gut content. The changes in the duration of these cycles were accompanied by appropriate changes in the free running time of both carbohydrate and amylase rhythms.